Photographs, - Zagelow, Gary Paul
Collection of color photographs documenting the buildings in Spokane. Most of the buildings are in the downtown area, though there are some in other parts of the city. Gary Paul Zagelow took most of the photographs and also organized the collection. The photographs are identified by street address, and sometimes by the name of the building. Numbered streets are interfiled with the named streets. Some streets have so many photographs that they are divided by the actual address. One particularly large part of the collection is the section on the Davenport Hotel. It is filed under Sprague Avenue and includes photographs before the restoration. It also includes photographs of the demolition of the Pennington section in 2000.